Rab5ab-Mediated Yolk Cell Membrane Endocytosis Is Essential for Zebrafish Epiboly and Mechanical Equilibrium During Gastrulation - Marsal, Maria; Hernández-Vega, Amayra; Pouille, Philippe-Alexandre; Martin-Blanco, Enrique (Frontiers in Cell and Developmental Biology, 2021)
Morphogenesis in early embryos demands the coordinated distribution of cells and tissues to their final destination in a spatio-temporal controlled way. Spatial and scalar differences in adhesion and contractility are essential for these morphogenetic movements, while the role that membrane remodeling may play remains less clear. To evaluate how membrane turnover modulates tissue arrangements we studied the role of endocytosis in zebrafish epiboly. Experimental analyses and modeling have shown that the expansion of the blastoderm relies on an asymmetry of mechanical tension in the yolk cell generated as a result of actomyosin-dependent contraction and membrane removal. Here we show that the GTPase Rab5ab is essential for the endocytosis and the removal of the external yolk cell syncytial layer (E-YSL) membrane. Interfering in its expression exclusively in the yolk resulted in the reduction of yolk cell actomyosin contractility, the disruption of cortical and internal flows, a disequilibrium in force balance and epiboly impairment. We conclude that regulated membrane remodeling is crucial for directing cell and tissue mechanics, preserving embryo geometry and coordinating morphogenetic movements during epiboly.